Izkušnje medicinskih sester v patronažnem varstvu z obiski na domu v okviru projekta Nadgrajena celovita obravnava pacienta - Ramšak-Pajk, Jožica (Obzornik zdravstvene nege, 2017)
Introduction: Community nursing is an important link in identifying, monitoring and addressing chronic diseases at the primary level. The purpose of the study is to present the views and experience in terms of upgraded preventive treatment and home visits. Methods: The mixed research design was used. Data were collected using a semi-structured questionnaire (Cronbach % = 0.92). 50 registered nurses participated and the response rate was 81 % (n = 41). A thematic analysis of open-ended questions was done and the analysis was carried out using the PSPP tool: descriptive statistics, t-test, variance analysis, correlation analysis. Results: Respondents see an added value of preventive home visits in health education interventions (x = 4.34, s = 0.85), detection of risk factors (x = 4.12, s = 0.81) and maintaining the patients' quality of life (x = 4.10, s = 0.92). Their satisfaction is linked to the acceptance of visits by patients and families (r = 0.754, p < 0.001), benefit to the profession of community health nursing (r = 0.766, p < 0.001), and treatment of individuals with family (r = 0.693, p < 0.001). Thematic analysis highlighted two themes, namely (1) positive experiences with home visits and (2) negative experiences with home visits. Discussion and conclusions: Respondents supported innovation in preventive home visits, especially the possibility of a comprehensive treatment of the individual and his family. According to the study data, we suggest that the community nurses in community health care become an equal partner in a team of reference model practice at the national level.
Keywords: chronic condition; chronic diseases; community nursing; kronična bolezen; patronažna zdravstvena nega; presejanje; prevention; preventiva; screening